2019
DOI: 10.3390/ijms20051107
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Differentially Expressed mRNA, lncRNA and circRNA and Their ceRNA Networks in the Longissimus Dorsi Muscle of Two Different Pig Breeds

Abstract: Circular RNA (circRNA) and long non-coding RNA (lncRNA) are known to participate in adipogenesis and myogenic differentiation, but their impact on porcine muscle traits is not well understood. We compared their expressional profiles in the longissimus dorsi muscle of Chinese Huainan pigs (HN, the fat type) and Western commercial Duroc×(Landrace×Yorkshire) (DLY, the thin type) pigs, and 854 mRNAs, 233 lncRNAs, and 66 circRNAs (p < 0.05 and |log2FoldChange|>1) were found to be differentially expressed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 68 publications
5
79
1
Order By: Relevance
“…More and more studies revealed that ncRNAs played regulatory roles by ceRNA network on the basis of ceRNA hypothesis [21], and utilizing ceRNA network analysis have identified a lot of regulatory factors including lncRNAs, miRNAs and cirRNAs associated with some animal economic traits such as hair follicle cycle of cashmere goat and poultry meat quality [27,47]. Although some studies also have paid attention on ceRNA regulatory mechanism in muscle of pig [2,48], little information is available in ceRNA regulatory pork quality formation. In this study, fat-type SS with higher pork quality and lean-type YY with faster growth as two typical pig breeds were used to investigate the regulatory mechanism of pork quality formation by transcriptome analysis including screening differentially expressed RNA and constructing ceRNA network.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More and more studies revealed that ncRNAs played regulatory roles by ceRNA network on the basis of ceRNA hypothesis [21], and utilizing ceRNA network analysis have identified a lot of regulatory factors including lncRNAs, miRNAs and cirRNAs associated with some animal economic traits such as hair follicle cycle of cashmere goat and poultry meat quality [27,47]. Although some studies also have paid attention on ceRNA regulatory mechanism in muscle of pig [2,48], little information is available in ceRNA regulatory pork quality formation. In this study, fat-type SS with higher pork quality and lean-type YY with faster growth as two typical pig breeds were used to investigate the regulatory mechanism of pork quality formation by transcriptome analysis including screening differentially expressed RNA and constructing ceRNA network.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid progression of sequencing technology in recent years, advances were produced in regulatory mechanism of pork quality formation, especially non-coding RNAs (ncRNA) [2,14,15]. For example, miR-23a was identified to associate with the composite of slow myosin heavy chain isoforms [16], and miR-17-5p was found to reduce preadipocyte differentiation by inhibiting some targets such as FABP4 and PPARG [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, ceRNET is mainly used to solve human cancer treatment, among which the typical representative is the construction of PTEN's ceRNET. In addition, ceRNET has also been applied to explore biological characteristics in animal and plant research (Qiu et al, 2018;Bai et al, 2019;He et al, 2019;Li et al, 2019;Wang et al, 2019a). It is reasonable to hypothesized that ceRNET would be an exactly effective methods to reflect the complete and accurate regulate process of the antler rapidly development.…”
Section: Introductionmentioning
confidence: 99%
“…Except for linear transcripts like miRNA, lncRNAs, and mRNAs, numerous circular RNAs (circRNAs) responsible for skeletal muscle development have been identi ed through the introduction of high throughput sequencing technology [19][20][21]. circRNAs are newly discovered non-coding RNA molecules with a closed-loop structure and acting as gene regulators in most organisms [22,23].…”
Section: Introductionmentioning
confidence: 99%